A 2-tuple linguistic multi-period decision making approach for dynamic green supplier selection (2017)
Green supplier selection aims to choose the best supplier, among several alternatives, taking into account not only traditional criteria such as cost and quality of service or product, but also considering the ability to produce these products or services fulfilling environmental standards or regulations and with the least negative impact on the environment. In real green selection contexts, sometimes a single static evaluation of suppliers is not enough for a conclusive decision and it is necessary to analyze suppliers’ evolution throughout different moments. Obviously, some parameters are not constant over time, rather they are dynamic and change from one period to another. Consequently, decisions about suppliers take place in a dynamic environment, where the final decision is made after an exploratory process. Besides, the available information is vague or imprecise that does not involve probabilistic uncertainty. In such situations, the use of 2-tuple linguistic model provides a convenient way to represent linguistic assessments through linguistic variables and to model uncertainty. In this paper, the main focus is on finding the right supplier by using a multi-criteria multi-period decision making approach based on the 2-tuple linguistic computational model.